Single-cell and bulk transcriptomics reveal a CD8+ T-cell gene signature predicting prognosis in diffuse large B-cell lymphoma - Liu, Hengqi; Feng, Yingfang; Qian, Zhengzi; Song, Zheng; Zhang, Ning; Yu, Jingwei; Liu, Xia; Qiu, Lihua; Zhou, Shiyong; Gong, Wenchen; Meng, Bin; Abolhassani, Hassan; et al. (Frontiers in Immunology, 2025)
BackgroundDiffuse large B-cell lymphoma (DLBCL) exhibits immunological heterogeneity that influences outcomes of immunochemotherapy, with CD8+ T cells playing a critical role in patient prognosis.MethodsWe integrated single-cell and bulk transcriptome data to establish a CD8⁺ T cell–associated prognostic signature. Single-cell RNA sequencing data from 29 samples (28 individuals), including DLBCL and reactive lymph nodes/tonsils, were analyzed to characterize CD8⁺ T cell heterogeneity, identify distinct subsets, and screen differentially expressed genes. Least absolute shrinkage and selection operator (LASSO) regression combined with multivariable Cox analysis was applied to bulk RNA-seq datasets to construct a prognostic model.ResultsAnalysis of 19,483 CD8⁺ T cells revealed eight transcriptionally distinct subsets, from which 48 genes were associated with clinical outcomes. Eight prognostic genes were incorporated into a CD8⁺ T cell–related signature, with higher CD69 and CD70 expression correlating with inferior survival. The signature effectively stratified patients into high- and low-risk groups that differed in cell-of-origin subtype, mutational landscape, and immune microenvironment characteristics. Moreover, the model showed potential to predict baseline response to chimeric antigen receptor T-cell (CAR-T) therapy.ConclusionThis study highlights CD8+ T cell heterogeneity in DLBCL and establishes a prognostic gene signature that informs patient survival prediction and CAR-T therapy efficacy.